Study of α-amylase and lipase enzymes of awassi sheep fed by levels of dietary protein and probiotic additives - Al-Abedi, Amal F.; Saeed, Ali A.; Al-Huosyney, Khalida S. (Journal of Kerbala for Agricultural Sciences, 2020)
Little studies about enzymes functions in ruminants inspired us to perform the present study. Enzymes are naturally produced by living cells to cause specific biochemical reactions to catalyze the degrative reactions by which substrates are digested into substrates’ chemical compounds. These simple compounds are used in turn for cell growth. α-amylase and lipase are considered important enzymes for this process. The present study was undertaken to investigate the effect of levels of dietary protein and probiotic additives ( Live Saccharomyces cerevisiae more than 3.0X1013 CFU and bacillus subtilis more than 4.0 X109CFU) on α-amylase and lipase of Awassi sheep. Sixteen Awassi sheep used in this study, Animals grouped to four classes (four animals in each group). The first class fed with crude protein(cp) (12%) with no probiotics, the second class fed with cp(12%) plus 1 kg/ton probiotic, the third class fed with cp(14%) with no probiotics, and finally the fourth one fed with cp(14%) plus 1 kg/ton probiotic. The main results have shown that there is significant increase (P<0.01) in the α-Amylase concentration between class cp(12%) comparing with class cp(14%). Regarding the interaction treatments, there is a significant increase (P<0.05) between cp(12%) plus no probiotic comparing with cp(14%) plus no probiotic, and comparing cp(12%) plus no probiotic with cp(14%) plus 1kg/ton probiotic, and between cp(12%) plus probiotic comparing with cp(14%) plus no probiotic. Regarding lipase, results haven’t shown any significant differences among any classes whether in main effects or in interaction treatments. We could conclude that, in the main effects, α-amylase concentration is increased by dietary protein cp(12%) more than cp(14%). And in the interaction treatments, α-amylase concentration is increased by dietary protein cp(12%) plus probiotic more than cp(14%) plus probiotic. Concerning lipase, there aren’t effects on lipase concentration by dietary protein cp(12%) and cp(14%) plus with or without probiotic.